The Value of Voice in an Experimental Labor Market - Vanessa Mertins (Verein für Socialpolitik, 2010)
Procedural fairness research has argued that giving people a voice in decision-making procedures leads to increased outcome satisfaction and enhanced compliance with decisions. The impact of voice on agents' motivation to perform well is investigated in a simple gift-exchange experiment, thereby testing the fair wage-fair process-effort hypothesis. Before principals set wages, they decide whether or not to allow agents to voice their opinion by communicating their desired wages. Agents respond to principals' wage offers and voice/no voice choices by choosing effort levels. We find a significant impact of voice on average effort levels. Principals who (a) give agents a voice and (b) offer high wages induce, on average, a higher performance and hence earn higher payoffs than principals who offer the same wage without voice. However, we also observe negative voice effects: agents who are given voice react to low wages with lower efforts than agents who were not given voice. Thus, a voice that is perceived to have no influence is even more detrimental than not giving a voice at all.
Keywords: C91; J31; M55; 330; experiment; gift exchange; incentives; incomplete contract; labor market; procedural fairness; voice